Struggles and Dilemmas of Uyghur Immigrants in Turkey: - Beydulla, Mettursun (Poligrafi, 2021)
The social and economic integration of the Uyghurs into Turkish society reflects a problem to which policy makers have not yet found a response. Marginalized by the larger society and separated by linguistic differences and cultural and social life-styles, a significant proportion of Uyghurs, especially “newcomers” who have arrived since the 1980s, is in danger of becoming part of a “parallel society.” This is reinforced by exclusion, inferiorization and “otherness,” restricted educational achievements, uncertain citizenship, legal status limbo and low socioeconomic status. Pro-Uyghur, pro-independence and anti-Chinese government mobilization in Turkey has attracted the attention of Chinese authorities for a long time, and this attention has in turn affected and shaped mobilization in Turkey. The Turkey-China relationship is involved as well. The main goals of Chinese policy and strategy in Turkey are the security of “Xinjiang Uyghur Autonomous Region” (a.k.a. East Turkistan), access to natural resources, security of the Belt and Road Initiative (BRI) and economic and technological investment. It means that China believes it must consolidate its control of “Xinjiang” (East Turkistan) and restrain the Uyghur independence movement in Turkey. China’s economic and technological power and investments in Turkey are not just increasing its influence; they are making Turkey far more reticent to speak out about Beijing’s abuses, systematic oppression and atrocities in the “Xinjiang” (East Turkistan). China’s geo-economic strategy has resulted in political influence in Turkey that profoundly affects its Uyghur population.